An analysis of COVID-19 and spirituality among African Christian women - Benson O. Igboin (HTS Teologiese Studies/Theological Studies, 2023)
There has been increasing research into the COVID-19 pandemic and the theological responses to it. However, not much research has been done on the COVID-19 and how women, particularly in Africa, utilised spiritual resources to respond to the pandemic. This article sought to bridge this gap. The article utilised both descriptive and analytical methods, and argued that many African women were more concerned about the health of the community than their male counterparts who concentrated more on arguments about the pandemic. Gleaning from our ethnographic data carried out from the Christ Apostolic Church and the Spirit and Life Family Bible Church in Nigeria, the article used Galen Watts’ theory of ‘spirituality of and for’ to analyse how African Christian women deployed their spirituality and resources to address the existential challenges the pandemic posed. It argued that the African Christian women shunned the ‘spirituality of’ argument that relates with discursive functions of being spiritual, which does not correspond to its practical application, and adopted ‘spirituality for’ which resonates with how spiritual resources are deployed to (re)solve existential challenges towards human flourishing. This, it argued, aligns much with the theology of The Circle of Concerned African Women Theologians.